New insights into structural features and optimal detection of circulating tumor DNA determined by single-strand DNA analysis. (December 2018) - Sanchez, Cynthia; Snyder, Matthew; Tanos, Rita; Shendure, Jay; Thierry, Alain
Abstract Circulating cell-free DNA (cfDNA) has received increasing interest as an apparent breakthrough approach in diagnostics, personalized medicine, and tumor biology. However, the structural features of cfDNA are poorly characterized. Specifically, the literature has discrepancies with regards to cfDNA size profile. We performed a blinded study of the distribution of cfDNA fragment sizes in cancer patient plasma (n = 11), by various ultra-deep-sequencing approaches and quantitative PCR (Q-PCR). Whole-genome sequencing of single-stranded DNA library preparation (SSP-S) revealed that nearly half of the total cfDNA fragment number are below 120 nucleotides, which are not readily detectable by standard double-stranded DNA library preparation (DSP) protocols. Fractional size distribution of cancer patient circulating DNA was very similar using both SSP-S-based or Q-PCR-based methods also revealing that high molecular weight (over 350 bp) cfDNA is a minor component ( 2%). These extra small detected cfDNA fragments may mostly result from nicks occurring in blood circulation in one or both DNA strands, which are subsequently revealed through the denaturation step of the SSP and Q-PCR procedures. Detailed analysis of the data suggested that most of the detectable cfDNA in blood has a nucleosome footprint (∼10-bp periodicity repeats). The nucleosome is thus the most stabilizing structure of DNA in the circulation. cfDNA molecules, which are initially packed in chromatin, are released from cells and are then dynamically degraded in blood both within and between nucleosomes or transcription factor-associated subcomplexes. While this study provides new insights into cfDNA size profiles harmonizing sequencing and Q-PCR findings, our data validate the use of a specific Q-PCR method and SSP-S for obtaining an optimal qualitative and quantitative analytical signal. Cancer: Short tumor DNA abundant, yet missed by blood tests Around half of all tumor-derived DNA strands found in the bloodstream of cancer patients are too short for detection by the most commonly used diagnostic sequencing methods. Alain R. Thierry from the Montpellier Cancer Research Institute, France, and colleagues quantified the size distribution of circulating cell-free DNA (cfDNA) using two genomic protocols that analyze single-stranded DNA—and can thus pick up small DNA fragments that are missed by conventional double-stranded approaches. Looking in the blood of patients with tumors of the colon, lung, breast and liver, the researchers showed that nearly half of all stretches of cfDNA are shorter than 120 nucleotides long. These sequences likely result from tightly packed DNA that's dynamically degraded into smaller and smaller fragments. The findings highlight the need for whole-genome sequencing or other single-stranded methods to get an accurate read on cfDNA profiles.